2014
DOI: 10.1038/ncomms4746
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutrition at conception modulates DNA methylation of human metastable epialleles

Abstract: In experimental animals, maternal diet during the periconceptional period influences the establishment of DNA methylation at metastable epialleles in the offspring, with permanent phenotypic consequences. Pronounced naturally occurring seasonal differences in the diet of rural Gambian women allowed us to test this in humans. We show that significant seasonal variations in methyl-donor nutrient intake of mothers around the time of conception influence 13 relevant plasma biomarkers. The level of several of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
381
1
9

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 442 publications
(424 citation statements)
references
References 21 publications
33
381
1
9
Order By: Relevance
“…Of note are studies of metastable epialleles, epigenetically labile regions of the genome that are subject to large changes in response to environmental influences during very early embryogenesis. These regions were first described in mice, but subsequent human studies in Gambia have demonstrated epigenetic variation at metastable epialleles that are linked to periconceptional maternal nutrition 77 , findings that have later been replicated in a rural Bangladeshi cohort 78 . The methylation status of metastable epialleles has been linked to later obesity and metabolic function 79 .…”
Section: Periconceptional Mechanismsmentioning
confidence: 94%
“…Of note are studies of metastable epialleles, epigenetically labile regions of the genome that are subject to large changes in response to environmental influences during very early embryogenesis. These regions were first described in mice, but subsequent human studies in Gambia have demonstrated epigenetic variation at metastable epialleles that are linked to periconceptional maternal nutrition 77 , findings that have later been replicated in a rural Bangladeshi cohort 78 . The methylation status of metastable epialleles has been linked to later obesity and metabolic function 79 .…”
Section: Periconceptional Mechanismsmentioning
confidence: 94%
“…A very small proportion of individuals (65) from the end of cohort enrollment also had food-frequency data, allowing for adjustment for folic acid intake in a subset of the population because methyl donor intake might be associated with offspring DNA methylation. 47 We also re-analyzed our data excluding the one current smoker in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…10 Other studies have demonstrated the presence of stochastic and global epigenomic changes following environmental exposures in mice 1,11 and humans. 12 In order to facilitate translation of animal studies that identify epigenetic biomarkers of environmental exposure and disease risk to human health and disease prevention, studies must demonstrate epigenetic changes not only at a single time point but across the life-course, and validate with mechanistic and epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%